Eco-Sufism Educational Design: Overcoming The Equality Of The Environmental Crisis In The 21st Century - Wahyudi, Annisa Rezki Eka Putri; Wahab, Wahab; Kurniawan, Syamsul (Al-Ulum: Jurnal Pendidikan Islam, 2025)
This study aims to design an education model based on Eco-Sufism as an alternative approach to addressing the global environmental crisis. Using a qualitative library research method, this study analyzes literature on Nasr's ideas and their application in education. The findings reveal that Eco-Sufism-based education has significant potential in fostering ecological awareness rooted in spirituality. This educational design promotes harmony between humans, nature, and God, emphasizing humanity's role as stewards responsible for environmental preservation. The integration of Sufism values into the educational curriculum offers a holistic approach relevant to the 21st century, positioning Islam as a pioneer of global ecological solutions rooted in spirituality. This study concludes that Eco-Sufism education can be an effective model for building sustainable ecological awareness, providing a transformative contribution to addressing global environmental challenges with a transcendental approach.